Effectiveness of Mobile Library Services Based on the LibQUAL+™ Method at the Pariaman City Library and Archives Office - Selvia Syaheri; Elva Rahmah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Mobile library services play a crucial role in expanding access to information for communities with limited access to permanent library facilities. However, continuous evaluation is necessary to ensure that service quality meets users' expectations and information needs. This study aimed to evaluate the effectiveness of the mobile library service provided by the Library and Archives Office (DISPERSIP) of Pariaman City using the LIBQUAL+™ framework. A quantitative descriptive approach was employed, involving 71 respondents selected through purposive sampling. Data were collected using a structured questionnaire based on the three LIBQUAL+™ dimensions: Affect of Service, Information Control, and Library as Place, and were analyzed using descriptive statistics. The findings indicate that the overall mobile library service was effective, with a mean score of 3.04. Affect of Service achieved the highest rating and was categorized as highly effective, whereas Information Control and Library as Place were classified as effective, with Information Control receiving the lowest evaluation. The study concludes that librarians' competence represents the primary strength of the service, while improvements in collection development and information resource management remain necessary. These findings provide practical guidance for enhancing the quality and sustainability of mobile library services.